Pengaruh Rasio Keuangan terhadap Kinerja Keuangan PT Astra Internasional Tbk - Diana Diana (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
This study aims to identify the effect of financial ratios of liquidity ratio, solvency ratio, activity ratio and profitability ratio on the financial performance at PT Astra International Tbk. The financial Ratios as an independent variable (X) consists of Liquidity Ratio (X1) which is analyzed bycurrent ratio, quick ratio and net working capital to total assets ratio, Solvency Ratio (X2) which is analyzed by total debt to assets ratio assets, total assets, debt to equity ratio and long-term debt to equity ratio; Activity Ratio (X3) which is analyzed by total asset turnover, working capital turnover and inventory turnover, and Probability Ratio (X4) which is analyzed by gross profit margin ratio, net profit margin ratio, operating ratio, rate of return on equity and rate of return on assets. The dependent variable (Y) in this study is a financial performance which is analyzed based on the net income (sales) (Y1), the net profit after tax (Y2), and the earning per share (Y3). The financial data of PT Astra International Tbk. used for this study were taken over five (5) years from 2010 - 2014. Analysis of Partial Least Square (PLS) using Smart PLS software version 20.0 was used as thedata analysis technique. The results showed that first hypothesis (H1), Liquidity Ratios had a significant effect on financial performance. A positive path coefficients of 0.289 with Tvalue 4.428 is bigger than Ttable or T (0.050; 5) = 2.776, meaning that the liquidity ratio significantly influences the financial performance. So the first hypothesis (H1) is accepted, which means that the liquidity ratio has a significant effect on the financial performance. The second hypothesis (H2), Solvency Ratio hasa significant effect on financial performance. A positive path coefficient of 0.334 with Tvalue15.563 is bigger than Ttable or T (0,050; 5) = 2,776, meaning that the Solvency Ratio significantly influences the Financial Performance. So the second hypothesis (H2) is accepted, which means that the Solvency Ratio has a significant effect on the financial performance. The third hypothesis (H3), Activity Ratio has asignificant effect on the financial performance. A positive path coefficient of 0,034 with Tvalue0.486 is smaller than Ttable or T (0,050; 5) = 2,776, meaning that the ratio of activity does not have a significant influence on the financial performance. So the third hypothesis (H3) is rejected, which means that the Activity Ratio has no significant effect on the financial performance. The fourth hypothesis (H4), Profitability Ratio has a significant effect on the financial performance. A positive path coefficient of 0.778 with Tvalueof 6.003 is bigger than Ttable or T (0,050; 5) = 2,776, meaning that the Profitability Ratio significantly influences the financial performance. So the fourth hypothesis (H4) is accepted, which means that the profitability ratio have a significant effect on the financial performance.Keywords: Financial Ratios, Financial Performance.